Numerical modelling of a PV-T collector working as evaporator in a solar assisted heat pump. (August 2020) - Zanetti, E; Del Col, D
Abstract: A numerical study of a PV-T collector working as an evaporator for a solar assisted heat pump is presented. The work has been realized in the framework of the SolairHP project for the study of a reversible dual source heat pump. The main objective is to increase the seasonal coefficient of performance of the heat pump compared to an air source heat pump and reduce the overall electrical consumption by including a solar collector-evaporator. A mathematical steady state model of the solar evaporator device has been realized in Matlab environment: it considers the energy and mass fluxes in three dimensions by working a discretization of the main surfaces of the PV sandwich and of the absorber plate (roll-bond plate). The input of the model are the ambient conditions (irradiance components and air temperature), the thermodynamic conditions of the refrigerant at the inlet (enthalpy and mass flowrate) and the circuitation. The main results of the model are the electric and thermal efficiency, the conditions of the refrigerant all along the channels and the temperature distribution on the PV-T surfaces. The numerical model has been used in the design procedure of the solar evaporators to be coupled to a 8 kW heat pump working with R32. A preliminary seasonal analysis on the PV-T evaporator has been realized in order to evaluate the advantage of the dual source system.